The Role of Ethnography in Enriching and Developing the Uzbek Language (Texas Journal of Multidisciplinary Studies, 2023)
In this article, the role of ethnography in the emotional expressive enrichment of the language is shown on the example of the development periods of Uzbek folk art, folklore, and history. It has been shown that the importance of national history and ethnography is high in the development of the language and its spread to the masses.